The privilege of King Casimir III on August 22, 1352 HISTORICAL AND PHILOLOGICAL PERSPECTIVE: HISTORICAL FLOOR, STRUCTURE OF THE DOCUMENT, TRANSLATION, COMMENTS (City: History, Culture, Society, 2019)
Privilege 1352 - the first known document of Casimir III concerning the city of Lviv, issued to the descendants of the Lviv warrior Berthold and certifying the right to eternal possession of the estates.